Coercive sanctions and international conflicts a sociological theory - Jaeger, Mark Daniel (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2018)
Perhaps the most common question raised in the literature on coercive international sanctions is: "Do sanctions work?" Unsurprisingly, the answer to such a sweeping question remains inconclusive. However, even the widely-presumed logic of coercive sanctions ? that economic impact translates into effective political pressure ? is not the primary driver of conflict developments. Furthermore, existing rationalist-economistic approaches neglect one of the most striking differences seen across sanctions conflicts: the occurrence of positive sanctions or their combination with negative sanctions, implicitly taking them as logically indifferent